Public Trust and Confidence towards Judiciary of Nepal: A Study based on Nepal National Governance Survey 2017/18 (Journal of Governance and Development (JGD), 2020)
Citizens’trust and confidence occupy central place in democratic governance. They are more vital in public organizations. The level of trust and confidence of the people towards any institution shows the performance level of that organization. This paper tries to look at the level of trust and confidence towards the court system (judiciary) in Nepal. In order to analyze the level of trust and confidence level, this paper has used the data base of Nepal National Governance Survey, 2017/18 conducted by Nepal Administrative Staff College (NASC) in a sample size of 12,872 individuals across 43 districts (out of 77) of Nepal. The study uses simply descriptive method of data presentation. The study finds that the level of trust and confidence of the people towards courts in Nepal is quite satisfactory. It also reveals that level of honesty is comparatively better for courts in comparison to civil service and bureaucracy, NGOs and political parties. Though there is slight difference in the perception of respondents from different demographic groups and regions on the issue of trust and confidence, no significant difference is marked among these groups. However, it is evident that courts need to make their services better, respond the clients properly, give impartial judgment, and curtail corruption in order to have more public trust and confidence.